2008
DOI: 10.1007/s00113-008-1456-2
|View full text |Cite
|
Sign up to set email alerts
|

Wirbelsäulenverletzung im Sport

Abstract: The current management of injuries of the spine effectuates a high rate of resumption of sports activity following conservative or operative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Postoperative chest tube output can be lower using VATS 9 , similar 16 or higher compared to OTC 20,25 . Minor complications directly attributed to VATS include pleural effusions indicating puncture or prolonged chest tube drainage (that might be due to the inability of suture closing the pleura), pneumothorax formation, and an increased rate of atelectasis and mucoid plug formation during collapsed lung surgery 10,16,19,[37][38][39] . Serious complications previously reported include lung injuries, the development of tension pneumothorax, neurologic injury and serious arterial bleeding indicating urgent conversion to OTC 12,20,23,38,[40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative chest tube output can be lower using VATS 9 , similar 16 or higher compared to OTC 20,25 . Minor complications directly attributed to VATS include pleural effusions indicating puncture or prolonged chest tube drainage (that might be due to the inability of suture closing the pleura), pneumothorax formation, and an increased rate of atelectasis and mucoid plug formation during collapsed lung surgery 10,16,19,[37][38][39] . Serious complications previously reported include lung injuries, the development of tension pneumothorax, neurologic injury and serious arterial bleeding indicating urgent conversion to OTC 12,20,23,38,[40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…The study showed a significant follow-up-dependant drop in the prevalence of sequels following VATS. Recently, a German group 39 presented the results of VATS for anterior reconstruction in 60 spinal fractures. Assessment included a physicians' judgement on the perceived ArM in four grades (grade 4 resembles disabling pain).…”
Section: Discussionmentioning
confidence: 99%
“…Fractures in the region of the thoracic and lumbar spine are common entities representing 80% of all vertebral fractures [ 1 ]. Almost half (49.6%) of vertebral body fractures are reported to be burst or incomplete burst fractures [ 2 , 3 ]. Thereof, the majority (68%) of these fractures occur at the thoracolumbar junction (Th11-L2) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Auch Könings und Böhmer (2000) sehen in der dorsalen Vorgehensweise ein relativ "komplikationsarmes, effektives und etabliertes Stabilisierungsverfahren". Sie Eine aktuellen Studie über "Wirbelsäulenverletzungen im Sport" (Merkel et al 2008) konnte zeigen, dass eine dorso-ventrale Versorgung den geringsten postoperativen Korrekturverlust aufweist, wobei hier noch keine Langzeitergebnisse vorlagen. Auch wenn der Korrekturverlust bei dem kombinierten Verfahren geringer war, gab es hinsichtlich der Rückenfunktion der Patienten, die anhand des VAS klassifiziert wurden, keine signifikanten Unterschiede zwischen dem rein dorsalen und dem kombinierten dorso-ventralen Verfahren (Merkel et al 2008).…”
Section: Behandlungsstrategien Von Thorakolumbalen Frakturenunclassified